Recent Advances in Local Anesthesia: Review of Literature (Academia Journal of Medicine, 2024)
Even if local anaesthetic remains the mainstay of pain  management in dentistry, research will continue to hunt  for innovative and more effective strategies to control the  pain. The majority of research efforts are focused on  developing anaesthetic medicines, delivery systems, and  related approaches. Modern dentistry techniques enable  dentists to provide better pain management with less  painful injections and unfavourable side effects. The  current review of the literature aims to compile persuasive  evidence for dentists about the use of modern local  anaesthetics, various techniques, and tactics to lessen pain  while delivering anaesthesia and so enhance patient  comfort.
Keywords: Anesthesia; Pain; Local anesthesia; Recent advances